Strengthening ASEAN-Guangxi Trade Relations: Enhancing Regional Integration and Industrial Collaboration - Wei, Chunyang; Shen, Qinjie (American Journal of Business Science Philosophy, 2025)
A complex array of global disruptions—including the COVID-19 pandemic, the US-China trade war, the Russia-Ukraine conflict, retaliatory tariffs, economic stagflation, supply chain breakdowns, and the rise of artificial intelligence technologies—has significantly challenged the foundational structure of regional economic development. This study investigates the key barriers hindering ASEAN–Guangxi trade from achieving sustainable and accelerated economic growth. Trade data from 2019 to 2024 were analyzed, and empirical data were collected through structured questionnaires administered to 200 business practitioners and policymakers across ASEAN member states and Guangxi. The data were processed and validated using the Statistical Package for the Social Sciences (SPSS). The results indicate that enhanced regional integration and the presence of positive spillover effects are pivotal in promoting sustainable trade relations between ASEAN and Guangxi. These findings offer actionable insights for companies operating in the region and serve as a valuable reference for policymakers and future researchers seeking to strengthen regional economic cooperation. This study contributes to the literature by identifying integration and spillovers as critical drivers of resilient regional trade amid contemporary global uncertainties.
Keywords: trade; sustainability; spillover effect; ASEAN-Guangxi